Formulation development and optimization of polyox based quick dissolving film of quetiapine - A Sunita Chaudhary; B Ankit Chaudhary; A Tejal Mehta (Wolters Kluwer Medknow Publications, 2012)
Quick dissolving film prepared by various grades of polyox like Polyox N10,N80, N750 and N205. Polyox having excellent film forming capacity with rapid hydration power which leads to rapid disintegration of film upon contact with saliva. Film is optimized for concentration of polymer and plasticizer using CCD design. The tensile Strength, folding Endurance, % drug released at 10 min (Y10) and disintegration time were selected as dependent variables. The data revealed that 2% of polyox N 750 and 15% of PEG 400 showed excellent film forming property with rapid drug release profile.